Evaluation of Trends in Respiratory Support for Very Low Birth Weight Infants: A Population Based Study - Shamayal Mandokhel, Hina Ihsan, Sumaira Tahseen, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the trends in respiratory support for very low birth weight infants. Study Design: Cohort study Place and Duration of Study: Department of Paediatric Medicine Unit-2, Balochistan Institute of Child Health Services Quetta from 1st January 2021 to 31st December 2021. Methodology: Five hundred participants were enrolled. Data regarding maternal clinical history, neonatal clinical data using standardized and was recorded on a well structures questionnaire. Risk of bronchopulmonary dysplasia was considered as in those with discharge at 34-35 weeks without supplementation of oxygen required. Nitric oxide inhalation more than 4 hours’ addictive or contiguous was considered as treatment. Non intubated ventilation greater than four hours, continuous positive airway pressure through nose was delivered as respiratory support. Results: There were 74.7% male infants without bronchopulmonary dysplasia while 74.1% female infants were having bronchopulmonary dysplasia. The gestational age as mean in no bronchopulmonary dysplasia infants was 28±2.1 while it was 26±2.2 in bronchopulmonary dysplasia infants The mean birth weight was 1187±253 grams in without bronchopulmonary dysplasia infants whereas it was 891±246 grams in bronchopulmonary dysplasia infants. One and five minutes Apgar scoring increased in without bronchopulmonary dysplasia infants. Conclusion: Health improvement initiative programs and modern interventions should be formulated that highlights the use of non-invasive ventilation options to increase the quality of life and well-being of preterm neonates.